“There’s room to do more”: a mixed-methods study of the Temporary Assistance for Needy Families (TANF) diversion program and intimate partner violence in Georgia - Jahangir, Tasfia; Dahn, Conjay; Devakottai, Ria; Livingston, Melvin D.; Woods-Jaeger, Briana (Frontiers in Public Health, 2024)
Introduction: Intimate partner violence (IPV) is a risk factor for homicides and suicides. As poverty is both a predictor and a consequence of IPV, interventions that alleviate poverty-related stressors could mitigate IPV-related harms. Temporary Assistance for Needy Families (TANF), a monthly cash assistance program, is one such potential intervention. In the state of Georgia, the TANF diversion program, which provides a non-recurrent lump-sum payment to deter individuals from monthly TANF benefits, is an understudied component of TANF that may influence the efficacy of state TANF programs in supporting IPV survivors. Aim: This study quantifies and qualifies the role of Georgia’s TANF diversion program in shaping IPV-related mortality. Methods: This study relies on a mixed-methods sequential explanatory design. Using data from the Georgia Violent Death Reporting System (GA-VDRS), an interrupted time series analysis was conducted to estimate the effect of TANF diversion on IPV-related homicides and suicides. Semi-structured interviews were then administered with TANF policy experts and advocates, welfare caseworkers, and benefit recipients (n=20) to contextualize the quantitative findings. Results: The interrupted time series analysis revealed three fewer IPV-related deaths per month after implementing TANF diversion, compared to pre-diversion forecasts (coefficient=-3.003, 95%CI [-5.474, -0.532]). However, the qualitative interviews illustrated three themes regarding TANF diversion: (1) it is a “band-aid” solution to the access barriers associated with TANF, (2) it provides short-term relief to recipients making hard choices, and (3) its limitations reveal avenues for policy change. Discussion: While diversion has the potential to reduce deaths from IPV, it may be an insufficient means of mitigating the poverty-related contributors to IPV harms. Its limitations unveil the need for improved programs to better support IPV survivors.